Band engineering and tuning thermoelectric transport properties of p-type Bi0.52Sb1.48Te3 by Pb doping for low-temperature power generation. (1st March 2018) - Kim, Kwanlae; Kim, Gwansik; Lee, Hwijong; Lee, Kyu Hyoung; Lee, Wooyoung
Abstract: Herein, we report the results of a systematic study on the effect of Pb doping on the thermoelectric transport properties of p -type BiSbTe alloys to validate its potential applications for low-temperature power generation. The maximum power factor ( 4.4 mW m − 1 K − 2 ) at 300 K was obtained using 0.31 at.% Pb-doped Bi0.52 Sb1.48 Te3 and was found to originate from an enlarged density of states effective mass as a result of the band engineering effect. The maximum efficiency of thermoelectric power generation ( η max ) could be enhanced by 150% at Δ T = 220 K when the Pb concentration was optimized. Graphical abstract: The maximum power factor ( 4.4 mW m − 1 K − 2 ) at 300 K was obtained using 0.31 at.% Pb-doped Bi0.52 Sb1.48 Te3 and was found to originate from an enlarged density of states (DOS) effective mass as a result of the band engineering effect.